Estimating Exchange Rate Exposure over Various Return Horizons: Focusing on Major Countries in East Asia - Jeong Wook Lee; Sunghee Ahn; Sammo Kang (East Asian Economic Review (EAER), 2016)
In this paper, we estimate the exchange rate exposure, indicating the effect of exchange rate movements on firm values, for a sample of 1,400 firms in seven East Asian countries. The exposure estimates based on various exchange rate variables, return horizons and a control variable are compared. A key result from our analysis is that the long term effect of exchange rate movements on firm values is greater than the short term effect. And we find very similar results from using other exchange rate variables such as the U.S. dollar exchange rate, etc. Second, we add exchange rate volatility as a control variable and find that the extent of exposure is not much changed. Third, we examine the changes in exposure to exchange rate volatility with an increase in return horizon. Consequently the ratio of firms with significant exposures increases with the return horizons. Interestingly, the increase of exposure with the return horizons is faster for exposure to volatility than for exposure to exchange rate itself. Taken as a whole, our findings suggest that the so-called "exposure puzzle" may be a matter of the methodology used to measure exposure.
Keywords: F31; F41; O53; 330; Exchange Rate Exposure; Change in Exchange Rates; Exchange Rate Volatility; Stock Price; Exposure Puzzle